Monetary and fiscal policies in a heterogeneous‐agent economy. (31st July 2018) - Sun, Hongfei; Zhou, Chenggang
Abstract: We study the effects of long‐run inflation and income taxation in an economy where households face uninsurable idiosyncratic risks. We construct a tractable competitive‐search framework that generates dispersion of prices, income and wealth. We analytically characterize the stationary equilibrium and the policy effects on individual choices. Quantitative analysis finds that monetary and fiscal policies have distinct effects on macro aggregates, such as output, savings and wealth, income and consumption inequalities. There is a hump‐shaped relationship between welfare and the respective policies. Overall, welfare is maximized by a deviation from the Friedman rule, paired with distortionary income taxation. Résumé: Politiques fiscales et monétaires dans une économie où les agents sont hétérogènes . Les auteurs étudient les effets de l'inflation à long terme et de l'impôt sur le revenu dans une économie où les ménages font face à des risques idiosyncratiques non‐assurables. Ils construisent un cadre conceptuel concurrence‐recherche maniable qui génère la dispersion des prix, du revenu, et de la richesse. On caractérise analytiquement l'équilibre stationnaire et les effets des politiques sur les choix individuels. L'analyse quantitative révèle que les politiques monétaires et fiscales ont des effets distincts sur les agrégats macro‐économiques comme le produit et les épargnes, et sur les inégalités de richesse, des revenus et de la consommation. Il y a une relation en forme de bosse entre le bien‐être et les politiques respectives. Au total, le bien‐être est maximisé par une déviation de la règle de Friedman pairée avec la fiscalité sur le revenu discrétionnaire.